Aplikasi Program Pencegahan DBD terhadap Perilaku Masyarakat dalam Pengawasan dan Pemberantasan Jentik Nyamuk Demam Berdarah Dengue dengan Menerapkan Teori Health Belief Model - Yuyud Wahyudi; Lilis Sulistiya Ningrum (Jurnal Surya Medika (JSM), 2021)
Dengue Fever is a disease caused by the dengue virus with acute fever symptoms by entering the human bloodstream through the bite of a mosquito from the genus Aedes. Dengue Hemorrhagic Fever (DHF) has spread widely to all provinces in Indonesia. This disease often appears as an Extraordinary Event (KLB) with relatively high morbidity and mortality. Many dengue incidence rates make the application of the DHF prevention program by applying the theory of the Health Belief Model (HBM) as a prevention effort that can change the behavior of healthy and clean living. This HBM consists of four components: perceived susceptibility, perceived severity, perceived benefits, perceived barriers, and cues to action. Based on the results of the study, it was conducted from 16 November - 12 December 2020. This research used a Quasi-experimental research design with the One Group Pre Post-test design approach with a sample of Ngrancah Hamlet RT 25 RW 8 Senggreng Village residents using a total sampling technique. The analysis technique of this research is using univariate analysis. The results of this study indicate that the health belief model theory indicators in the DHF prevention program are close to a maximum value, namely Perceived Susceptibility with a mean value of 17.30, perceived severity with a mean value of 15.80, perceived benefits of 15.80, perceived barrier 16.70, and cues. To act with a mean value of 17.30. This study concludes that these results are expected to increase awareness for healthy and clean behavior in preventing DHF.